Intelecto agente, motor inmóvil y Dios en Aristóteles - Farieta, René (2019)
“Agent Intellect, Unmoved Mover and God in Aristotle”. This article faces the classic problem of the interpretation of what Aristotle calls in de An. III, 5 “the intellect that produces all things”, which is commonly named agent intellect. Historically, there have been two approaches: one that goes back to Alexander of Aphrodisias, who associates the agent intellect with the unmoved mover and the divinity, and another one, associated with Theophrastus but whose major representatives are Philoponus and St. Thomas of Aquinas, who consider that agent intellect is an exclusively human faculty. This last interpretation has been the most accepted historically. Nevertheless, in recent years there has been a resurgence of interpretations of the agent intellect as divine (Caston, Frede, Burnyeat, and others). What we want to demonstrate in this article is that this revival, more than responding to a reinterpretation of the agent intellect, is due to a different understanding of the divinity in Aristotle’s philosophy, which supposes immanent characteristics closer to the human intellect.